Lubricant-Infused Nanoparticulate Coatings Assembled by Layer-by-Layer Deposition - Vogel, Nicolas; et al. (Advanced Functional Materials, 2014)
Omniphobic coatings are designed to repel a wide range of liquids without leaving stains on the surface. A practical coating should exhibit stable repellency, show no interference with color or transparency of the underlying substrate and, ideally, be deposited in a simple process on arbitrarily shaped surfaces. We use layer-by-layer (LbL) deposition of negatively charged silica nanoparticles and positively charged polyelectrolytes to create nanoscale surface structures that are further surface-functionalized with fluorinated silanes and infiltrated with fluorinated oil, forming a smooth, highly repellent coating on surfaces of different materials and shapes. We show that four or more LbL cycles introduce sufficient surface roughness to effectively immobilize the lubricant into the nanoporous coating and provide a stable liquid interface that repels water, low-surface-tension liquids and complex fluids. The absence of hierarchical structures and the small size of the silica nanoparticles enables complete transparency of the coating, with light transmittance exceeding that of normal glass. The coating is mechanically robust, maintains its repellency after exposure to continuous flow for several days and prevents adsorption of streptavidin as a model protein. The LbL process is conceptually simple, of low cost, environmentally benign, scalable, automatable and therefore may present an efficient synthetic route to non-fouling materials.
Keywords: colloids; layer-by-layer; nanostructures; wetting; omniphobicity